Information and Communication Technology and Organizational Performance During Covid-19 Pandemic: The Role of Organizational Commitment, Growth Mindset, and Entrepreneurial Orientation - Li, Zhiwen; Akouatcha, Harold Guy; Akram, Umair; Anaba, Oswin Aganda (Frontiers in Psychology, 2021)
The purpose of this study is to assess how information and communication technology (ICT) adoption influences organizational performance (OP) during the Covid-19 pandemic by highlighting psychometric variables such as employees’ organizational commitment (OC), growth mindset (GM) and entrepreneurial orientation (EO). Based on the complementarity theory, we built a theoretical framework where OC, GM and EO mediate the influence of ICT on OP, and tested hypotheses proposed. Responses of 297 employees from agriculture cooperatives in Côte d'Ivoire were obtained on the basis of questionnaires which composed the data for this study. The empirical analysis affirmed the significant and positive effect of ICT adoption on OP, and the significant mediating effect of OC and GM in the relationship between ICT adoption and OP. However, the role of EO in mediating the influence of ICT adoption on OP is insignificant. This research increases understanding of the underlying process of the relationship between ICT adoption and organizational performance during the Covid-19 pandemic.